1998
DOI: 10.4315/0362-028x-61.9.1203
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Listeria monocytogenes in Milk by Pulsed Electric Field

Abstract: Pasteurized whole, 2%, and skim milk were inoculated with Listeria monocytogenes Scott A and treated with high-voltage pulsed electric field (PEF). The effects of milk composition (fat content) and PEF parameters (electric field strength, treatment time, and treatment temperature) on the inactivation of the bacterium were studied. No significant differences were observed in the inactivation of L. monocytogenes Scott A in three types of milk by PEF treatment. With treatment at 25 degrees C, 1- to 3-log reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
70
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(78 citation statements)
references
References 0 publications
8
70
0
Order By: Relevance
“…In other cases a very limited effect or no effect has been detected [5,13]. Concerning the effect of the temperature on microbial inactivation effectiveness, numerous authors observed that increasing the inlet temperature from 22 to 50 °C increased the sensitivity of microorganisms to PEF treatment [5,26,27]. This increase in the rate of inactivation with increasing temperature may be due to the decrease in the electric breakdown potential of the cell membrane, as previously suggested by Coster [6].…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…In other cases a very limited effect or no effect has been detected [5,13]. Concerning the effect of the temperature on microbial inactivation effectiveness, numerous authors observed that increasing the inlet temperature from 22 to 50 °C increased the sensitivity of microorganisms to PEF treatment [5,26,27]. This increase in the rate of inactivation with increasing temperature may be due to the decrease in the electric breakdown potential of the cell membrane, as previously suggested by Coster [6].…”
Section: Introductionmentioning
confidence: 65%
“…With the application of electric fields as short-duration pulses, minimal ohmic heating is generated and the process remains non-thermal. With regards to the effect of PEF on microorganisms and enzymes of milk, some controversial results have been obtained [2,3,5,11,12,19,22,25,26,28]. Table I shows that in several cases, high levels of microbial inactivation have been achieved, between 3-and 4.5-log reduction [10,11,28].…”
Section: Introductionmentioning
confidence: 99%
“…The increase in inactivation with temperature is attributed to a decrease in the electrical breakdown potential of the membrane (Reina et al, 1998), which increases the fluidity of the cell membrane, affecting its physical stability and decreasing the critical field intensity so that electroporation takes place ). value of 32.9, 14.7 and 7.14 s at 60, 72 and 75ºC of L. plantarum in sterile milk.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have observed that factors such as the presence of fat and sugar seem to protect the microorganism and enzyme against treatment (Bendicho et al, 2003 a). On the contrary, other studies do not show any significant effect of food composition on PEF microbial inactivation (Reina et al, 1998;Dutreux et al, 2000;Mañas et al, 2001). It seems that the different food constituents and target microorganism do not affect equally on the inactivation degree.…”
Section: Product Related Factorsmentioning
confidence: 98%
See 1 more Smart Citation